Paraoxonase-1 polymorphisms and cerebral ischemic stroke: a pilot study in mexican patients (Colombia Medica, 2018)
Background: The serum paraoxonase-1 (PON1) associated to HDL presents two common polymorphisms in the positions 192 and 55. These polymorphisms are considered determinant of the capacity of HDL to protect LDL from their oxidative modification. In this context, the PON1 genotype has been associated with cardiovascular diseases, including stroke.Objective: To determine the allelic and genotypic frequencies of PON1 L55M and Q192R as well as the enzymatic activities of PON1 in subjects with and without atherothrombotic stroke.Methods: There were included 28 people with atherothrombotic stroke and 29 without stroke. The genotyping was carried out by PCR-RFLP and the phenotyping by measurement of the activities of paraoxonase and arylesterase in serum.Results: For the polymorphism Q192R, the allelic frequencies (Q/R) were 0.46/0.54 and 0.48/0.52 (p= 0.843) for the control group and the group with stroke, respectively. While for the polymorphism L55M, the allelic frequencies (L/M) were 0.81/0.19 for the control group, and 0.78/0.22 for the group with stroke (p= 0.610). The activity levels of paraoxonase were not significantly different between the control and stroke groups (450 vs. 348 UI/mL, p= 0.093) While the activity levels of arylesterase were significantly different between the studied groups (90 vs. 70 UI/mL, p= 0.001); however, upon adjustment by multiple linear regression, it was not longer significant.Conclusion: The polymorphisms Q192R and L55M, and the paraoxonase activity of PON1 are not risk factors for atherothrombotic stroke according to the results of this study.